The Study on the Potential Incidence of Severe Thalassemia among Children Born to at-risk Partner of pregnant woman, Antenatal Care Clinic, Long Hospital, Phrae Province - Tuida, Kidjakarn (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2023)
This study were to 1) study the prevalence of pregnant women and their partners who tested positive for thalassemia carrier screening; 2) study the prevalence of at-risk couples who have the potential to have children with severe thalassemia; 3) study the incidence of severe thalassemia from the screening tests and 4) be used as part of planning for the prevention and control of thalassemia in Long Hospital. The sample were 467 pregnant women attending antenatal care at Long Hospital, Phrae Province. The results showed that pregnant women who gave positive and negative results for primary thalassemia screening accounted for 40.47 percent and 59.53 percent, respectively. The number of pregnant women who tested positive for thalassemia screening separately was 12.83 percent of the pregnant women who had DCIP test, and the erythrocyte index MCV<80 fL was 62.03 percent, and the DCIP test was positive with MCV<80 fL, representing 26.20 percent of the pregnant women who tested positive for thalassemia screening. At-risk couples of pregnant women who tested positive for thalassemia screening were found to have abnormal matching results. Both of them had to be sent for further testing, accounting for 28.04 percent and the husband who had the matching results found that the husband had a normal result representing 71.96 percent. The risk of pregnant women and husbands having abnormal results, both must be sent for further examination, it was found that the number of at-risk couples whose children were at risk and without the risk of severe thalassemia was 24.53 percent and 75.47 percent respectively. From the number of risk couples whose children are at risk of severe thalassemia, it can be classified as follows: Hb’ Bart’s hydrops fetalis 23.08%, Beta -thalasemia/Hb E Disease accounted for 61.54 percent and Beta thalassemia Disease accounted for 15.38 percent.